2015
DOI: 10.1111/2041-210x.12357
|View full text |Cite
|
Sign up to set email alerts
|

Mapping diversity indices: not a trivial issue

Abstract: Summary1. Mapping diversity indices, that is estimating values in all locations of a given area from some sampled locations, is central to numerous research and applied fields in ecology. 2. Two approaches are used to map diversity indices without including abiotic or biotic variables: (i) the indirect approach, which consists in estimating each individual species distribution over the area, then stacking the distributions of all species to estimate and map a posteriori the diversity index, (ii) the direct app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…The existing approaches for biodiversity mapping without including environmental data are shown to produce inaccurate spatial predictions of diversity indices (Granger et al, ). In this study, in general, the environmental data‐driven GAMs showed better predictive ability than the covariate‐free direct interpolation method (Table ), thus, supporting the inclusion of fine‐scale environmental, biotic and historical disturbance data for more accurate mapping of biodiversity indices when these data are available.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing approaches for biodiversity mapping without including environmental data are shown to produce inaccurate spatial predictions of diversity indices (Granger et al, ). In this study, in general, the environmental data‐driven GAMs showed better predictive ability than the covariate‐free direct interpolation method (Table ), thus, supporting the inclusion of fine‐scale environmental, biotic and historical disturbance data for more accurate mapping of biodiversity indices when these data are available.…”
Section: Discussionmentioning
confidence: 99%
“…Both habitat‐based and covariate‐free (direct interpolation methods such as Kriging) approaches have been used for mapping biodiversity indices. Although covariate‐free approaches have been criticized for low predictive ability (Granger et al, ), the relative performance of the approaches has rarely been tested using field data.…”
Section: Introductionmentioning
confidence: 99%
“…Estimating values of diversity over an area given a sample is crucial for a number of dierent ecological tasks (Granger et al, 2015 In some cases, spatial non-stationarity has been advocated as one of the major problems when the variability of a certain variable is non-uniform in space (Osborne et al, 2007). In our case, we would promote our approach to also account for potential anomalies, or simply spots of diversity variation in time, when measuring beta-diversity from satellites.…”
Section: Discussionmentioning
confidence: 99%
“…Information about communities, here defined as a taxonomic assemblage of distinct populations of species that co‐occur in a given space at a given time (Begon, Harper, & Townsend, ), is therefore essential to make informed decisions for conservation prioritisation (D'Amen et al., ; Guisan et al., ; Mateo, de la Estrella, Felicisimo, Munoz, & Guisan, ) and to create biodiversity indices (e.g. Essential Biodiversity Variables; Pereira et al., ) for policy decisions (Fleishman, Noss, & Noon, ; Granger et al., ).…”
Section: Introductionmentioning
confidence: 99%